2015
DOI: 10.1890/15-0300.1
|View full text |Cite
|
Sign up to set email alerts
|

Aboveground vertebrate and invertebrate herbivore impact on net N mineralization in subalpine grasslands

Abstract: Abstract. Aboveground herbivores have strong effects on grassland nitrogen (N) cycling. They can accelerate or slow down soil net N mineralization depending on ecosystem productivity and grazing intensity. Yet, most studies only consider either ungulates or invertebrate herbivores, but not the combined effect of several functionally different vertebrate and invertebrate herbivore species or guilds. We assessed how a diverse herbivore community affects net N mineralization in subalpine grasslands. By using size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 48 publications
1
53
1
Order By: Relevance
“…The impacts of insect herbivores, in particular, often rival or exceed those of their vertebrate counterparts [57], and insects often regulate plant biomass [8,9], increase species diversity [10], determine the outcomes of competitive interactions [6,11,12], and enhance nutrient recycling rates [4,5,13]. Since these processes result from plant consumption by, and subsequent growth of, insect herbivores, it is important to understand the nutritional constraints on insect performance and their subsequent community-level impacts.…”
Section: Introductionmentioning
confidence: 99%
“…The impacts of insect herbivores, in particular, often rival or exceed those of their vertebrate counterparts [57], and insects often regulate plant biomass [8,9], increase species diversity [10], determine the outcomes of competitive interactions [6,11,12], and enhance nutrient recycling rates [4,5,13]. Since these processes result from plant consumption by, and subsequent growth of, insect herbivores, it is important to understand the nutritional constraints on insect performance and their subsequent community-level impacts.…”
Section: Introductionmentioning
confidence: 99%
“…However, once released from grazing pressure, they can outcompete the other species due to faster growth rates (Lind et al 2013). As, again, Risch et al (2015) showed no differences in root biomass among our treatments in the tall-grass vegetation, this suggests that soil nutrients are not as readily available for plant uptake in this vegetation type (tall grass). In the tall-grass vegetation, forbs and legumes were also able to increase SLA when all herbivores were excluded (None), but this increase came at the cost of producing fewer leaves and therefore did not correlate with a change in dominance.…”
Section: Changes In Life Form Dominancementioning
confidence: 57%
“…Grasses increased in dominance by increasing tiller density, which may provide a competitive advantage (see also Sbrissa et al 2001). However, since the soil sustaining the short-grass vegetation is fairly nutrient rich for the constrained area of the SNP (Schütz et al 2006), andRisch et al (2015) showed increased soil N mineralization rates with progressive herbivore exclusion, our findings suggest that the mechanism behind the increased grass dominance was likely associated with increased soil nutrient exploitation. This could happen by decreasing the investment in root growth when grazing pressure is lowered (Milchunas and Lauenroth 1989) or by benefiting from the nutrient pools contained within the soil of nutrient-rich environments (Tilman 1988, Goldberg andLanda 1991).…”
Section: Changes In Life Form Dominancementioning
confidence: 73%
See 1 more Smart Citation
“…Risch et al . ) influence plant α‐ and β‐diversity levels in our study area, with the number of plant species ranging from <10 to over 50 per 1 m 2 .…”
Section: Methodsmentioning
confidence: 98%